Митний контроль у системі публічного управління сталим розвитком України в умовах інтеграції України до світового простору - Дум’як , Юрій Любомирович (Національний університет «Львівська політехніка», 2023)
У дисертаційній роботі наведено теоретичне узагальнення і вирішення наукового завдання, що полягає у теоретико-методологічному та функціональному обґрунтуванні основ здійснення митного контролю у системі публічного управління сталим розвитком України в умовах інтеграції України до світового простору. За своєю структурою дисертаційна робота складається із вступу, трьох розділів, поділених на підрозділи, висновку, списку використаних джерел та додатків. The thesis work presents a theoretical generalization and solution of a scientific problem, which consists in the theoretical, methodological and functional substantiation of the foundations for the implementation of customs control in the system of public management of sustainable development of Ukraine in the context of Ukraine's integration into the world space. According to its structure, the dissertation work consists of an introduction, three chapters, divided into subsections, a conclusion, a list of references and appendices.The introduction substantiates the relevance of the topic under study, formulates the purpose and objectives of the study, describes the novelty and practical significance of the results of the dissertation research.
Customs control in the system of public management of sustainable development of Ukraine in the context of Ukraine's integration into the world space
Keywords: митний контроль, митна справа, сталий розвиток, європейська інтеграція, митне оформлення, безпека, публічне управління, реформування системи державного управління, customs control, customs business, sustainability, european integration, customs clearance, security, public administration, reforming the state administration system.; 351.811.123.1:502.131.1